THE CORRELATION BETWEEN GRAMMAR AND VOCABULARY MASTERY TOWARD SPEAKING SKILL AMONG THE SEVENTH GRADE STUDENTS OF MTSN 1 KEDIRI - Sari, Galih Putri Kemala (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2019)
This research is aimed to know whether there is significant correlation between grammar and vocabulary mastery toward speaking skill among the seventh grade students of MTsN 1 Kediri. The design of this research was descriptive quantitative. The sample was 194 students. . The research instruments in this research were tests and questionnaire. The result was there is significant correlation between grammar and vocabulary mastery toward speaking skill among the seventh grade students of MTsN 1 Kediri. The value of correlation between X1 and Y is 0,46, then for correlation between X2 and Y is 0,234. It is recommended for the teachers to pay attention to the students’ speaking skill.